Intracellular HIV-1 Tat regulator induces epigenetic changes in the DNA methylation landscape - Rodríguez-Agustín, Andrea; Ayala-Suárez, Rubén; Díez-Fuertes, Francisco; Maleno, María José; de Villasante, Izar; Merkel, Angelika; Coiras, Mayte; Casanova, Víctor; Alcamí, José; Climent, Núria (Frontiers in Immunology, 2025)
IntroductionThe HIV regulatory protein Tat enhances viral transcription and also modifies host gene expression, affecting cell functions like cell cycle and apoptosis. Residual expression of Tat protein is detected in blood and other tissues even under antiretroviral treatment. Cohort studies have indicated that, despite virologic suppression, people with HIV (PWH) are at increased risk of comorbidities linked to chronic inflammation, accelerated immune ageing, and cellular senescence, sometimes associated with abnormal genomic methylation patterns. We analysed whether Tat influences DNA methylation and subsequently impacts the transcriptional signature, contributing to inflammation and accelerated ageing.MethodsWe transfected Jurkat cells with full-length Tat (Tat101), Tat’s first exon (Tat72), or an empty vector (TetOFF). We assessed DNA methylation modifications via the Infinium MethylationEPIC array, and we evaluated transcriptomic alterations through RNA-Seq. Methylation levels in gene promoters or body regions were correlated to their expression data, and subsequently, we performed an overrepresentation analysis to identify the biological terms containing differentially methylated and expressed genes.ResultsTat101 expression caused significant hyper- and hypomethylation changes at individual CpG sites, resulting in slightly global DNA hypermethylation. Methylation changes at gene promoters and bodies resulted in altered gene expression, specifically regulating gene transcription in 5.1% of differentially expressed genes (DEGs) in Tat101- expressing cells. In contrast, Tat72 had a minimal impact on this epigenetic process. The observed differentially methylated and expressed genes were involved in inflammatory responses, lipid antigen presentation, and apoptosis.DiscussionTat expression in HIV infection may constitute a key epigenetic modelling actor that contributes to HIV pathogenesis and chronic inflammation. Clinical interventions targeting Tat blockade may reduce chronic inflammation and cellular senescence related to HIV infection comorbidities.